A new species of Rodrigama Gauld (Hymenoptera: Ichneumonidae: Poemeniinae) from Israel: a significant range extension - Broad, Gavin R.; Kuslitzky, Wolf S. (Zootaxa, 2019)
Rodrigama freidbergi sp. nov. is described based on specimens collected in the last 30 years in Israel. Previously described Rodrigama species are found in Costa Rica, Japan, China and Taiwan so this discovery of a rather large and distinctive species so far West is noteworthy. Pimplaetus taishanensis He 1996 is newly transferred to Rodrigama as Rodrigama taishanense comb. nov.